Polymer composite film, composite current collector, preparation method of composite current collector, positive electrode and application of positive electrode
By providing a functionalized modification layer in the polymer composite film of the positive electrode composite current collector, the break elongation of the battery current collector is reduced, and the problem that the battery cannot be disconnected in time under thermal runaway is solved, which significantly improves the safety performance of the battery.
Patent Information
- Application Number
- CN202510389442.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-03-31
AI Technical Summary
The excessive elongation of the existing positive electrode composite fluid collector causes the battery to be unable to be disconnected in time when thermally out of control, continuously providing access, affecting battery safety.
A polymer composite film is used, which includes a polymer base layer and a first modified layer and a second modified layer disposed on both sides of the polymer base layer, respectively. The components of the modified layer include a functional polymer material, through which it cooperates with the polymer base layer to form a film layer with a lower elongation of break and a higher tensile strength.
It effectively reduces the break elongation of the battery current collector, so that it can break in time when it is damaged by external forces, cut off the abnormal current path inside the battery, avoid the battery from getting out of control, and significantly improve the battery's safety performance.
Smart Images

Figure CN119898103A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to a polymer composite film, a composite current collector and a preparation method thereof, a positive electrode and applications thereof. Background Art
[0002] At present, power batteries generally take high energy density and high rate as their iterative development goals, but the higher the energy density of lithium-ion batteries, the worse their safety is, and they are more likely to cause thermal runaway, which seriously restricts the further development of power batteries in the field of new energy. Among the types of battery thermal runaway, short circuit between negative electrode material and positive electrode material and internal short circuit between positive electrode current collector and positive electrode material are directly related to positive electrode current collector.
[0003] At present, composite current collectors are expected to gradually replace traditional current collectors due to their advantages of high safety, low cost, and high energy density. The existing positive composite current collectors are mainly composed of polyethylene terephthalate (PET) base film and aluminum metal layer. Among them, the insulation properties of PET itself enable the battery to reduce the risk of short circuit in cases such as thermal runaway. However, the elongation of the positive composite current collector generally exceeds 80%, and its excessively high elongation at break makes it impossible for the positive composite current collector to be disconnected in time when it is damaged by external force, and continues to provide a path for abnormal reactions inside the battery, which is not conducive to controlling battery thermal runaway. Therefore, appropriately reducing the elongation of the positive composite current collector can prevent the occurrence of battery thermal runaway. Summary of the invention
[0004] Based on this, the present application provides a polymer composite film, a composite current collector and a preparation method thereof, a positive electrode and an application thereof. The polymer composite film provided in the present application has a low elongation, and when used as a positive electrode current collector base film, it can effectively prevent the occurrence of thermal runaway of the battery.
[0005] In a first aspect of the present application, a polymer composite film is provided, the polymer composite film comprising a polymer base layer and a first modified layer and a second modified layer respectively disposed on two opposite side surfaces of the polymer base layer;
[0006] The material of the polymer base layer includes one or more of polyethylene terephthalate, polyethylene terephthalate-1,4-cyclohexanedimethanol and polyethylene terephthalate-1,4-cyclohexanedimethanol;
[0007] The components of the first modified layer and the second modified layer each independently include: a functionalized polymer material;
[0008] The functionalized polymer material includes one or more of polyethylene naphthalate, poly(m-phenylene adipamide), liquid crystal polymer, polyoxymethylene, polyphenylene sulfide and polyphenylene ether.
[0009] In one embodiment, the components of the first modified layer and the second modified layer independently include: a poly(terephthalate) polymer, an anti-blocking agent, and a functionalized polymer material.
[0010] In one embodiment, the raw materials for preparing the first modified layer and the second modified layer independently include: an anti-adhesive masterbatch and a modified masterbatch in a mass ratio of (1-5): (95-99);
[0011] The anti-blocking masterbatch comprises the polyterephthalate polymer and the anti-blocking agent;
[0012] Wherein, in the anti-blocking masterbatch, the mass ratio of the anti-blocking agent to the polyterephthalate polymer is (0.1-5): (95-99.9);
[0013] The modified masterbatch comprises the polyterephthalate polymer and the functionalized polymer material;
[0014] Among them, in the modified masterbatch, the mass ratio of the functionalized polymer material to the polyester terephthalate polymer is (20~60): (40~80).
[0015] In one embodiment, the polyethylene terephthalate polymer includes one or more of polyethylene terephthalate, polyethylene terephthalate-1,4-cyclohexanedimethanol and polyethylene terephthalate-1,4-cyclohexanedimethanol;
[0016] And / or, the anti-adhesive agent includes one or more of silicon dioxide, glass microspheres, calcium carbonate and talc;
[0017] In one embodiment, the polymer composite film has one or more of the following characteristics:
[0018] (1) The thickness ratio of the first modified layer to the polymer base layer is (0.6-1.4): (3.2-4.8);
[0019] (2) The thickness ratio of the second modified layer to the polymer base layer is (0.6-1.4):(3.2-4.8).
[0020] In one embodiment, the raw materials for preparing the first modified layer and the second modified layer independently further include: a nucleating agent; and the nucleating agent has one or more of the following characteristics:
[0021] (1) The mass ratio of the nucleating agent to the functionalized polymer material is (1-5): (20-60);
[0022] (2) The nucleating agent includes one or more of calcium carbonate, layered double metal hydroxide, boron nitride, zinc oxide, dibenzylidene sorbitol and aryl dicarbonamide.
[0023] In one of the embodiments, the polymer composite film further comprises: a first heat-conducting layer and a second heat-conducting layer;
[0024] Wherein, the first heat-conducting layer is arranged on a surface of the first modified layer which is away from the polymer base layer;
[0025] The second heat-conducting layer is disposed on a surface of the second modified layer that is away from the polymer-based layer.
[0026] In a second aspect of the present application, a composite current collector is provided, comprising the polymer composite film as described in any one of the embodiments of the first aspect of the present application, and a metal layer disposed on at least one surface of the polymer composite film.
[0027] In one embodiment, the material of the metal layer includes one or more of aluminum and aluminum alloy;
[0028] And / or, the thickness of the metal layer is 0.8 μm to 1.2 μm.
[0029] The third aspect of the present application provides a method for preparing the composite current collector according to the second aspect of the present application, comprising the following steps:
[0030] Vacuum evaporating the material of the metal layer on at least one side surface of the polymer composite film to prepare the composite current collector;
[0031] The process parameters of the vacuum evaporation have one or more of the following characteristics:
[0032] (1) The wire feeding speed of the material of the metal layer is 400 mm / min to 500 mm / min;
[0033] (2) The vacuum evaporation rate is 10 m / min to 20 m / min;
[0034] (3) The vacuum evaporation power is 7 kW to 12 kW;
[0035] (4) The temperature of the main roller of the vacuum evaporation is -20°C to 0°C;
[0036] (5) The rewinding tension and unwinding tension of the vacuum evaporation are independently 100N~300N;
[0037] (6) The distance between the heat source of the vacuum evaporation and the polymer composite film is 250 mm to 350 mm.
[0038] In a fourth aspect of the present application, a positive electrode is provided, comprising the composite current collector described in the second aspect.
[0039] In a fifth aspect of the present application, a battery is provided, comprising the positive electrode described in the fourth aspect.
[0040] In a sixth aspect of the present application, there is provided an electrical device comprising the battery described in the fifth aspect.
[0041] The polymer composite film provided in the present application has at least the following beneficial effects:
[0042] The polymer composite film provided by the present application includes a first modified layer and a second modified layer respectively disposed on the surfaces of the opposite sides of the polymer base layer, and the components of the first modified layer and the second modified layer include a specific type of functionalized polymer material, wherein, under the mutual cooperation of the specific type of functionalized polymer material and the polymer base layer of the specific material, the first modified layer and the second modified layer can form a film layer with a lower elongation at break and a higher tensile strength on the surface of the polymer base layer. Furthermore, the lower elongation at break of the first modified layer and the second modified layer enables the polymer composite film of the present application to be used as a battery current collector base film, and when it is subjected to external forces such as battery collision or breakdown, it can be easily broken, and then the abnormal current path inside the battery can be cut off in time, so that the battery forms multiple short circuits, thereby effectively avoiding thermal runaway of the battery caused by continuous power supply, and significantly improving the safety performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0044] Figure 1 A schematic diagram of the structure of a polymer composite membrane provided as an example of the present application;
[0045] Figure 2 A schematic diagram of the structure of a polymer composite membrane provided as another example of the present application;
[0046] Figure 3 A schematic diagram of the structure of a positive electrode current collector provided in an example of the present application;
[0047] Figure 4 A schematic diagram of the structure of a positive electrode current collector provided for another example of the present application.
[0048] In the figure, 10-polymer composite film; 110-polymer base layer; 120-first modified layer; 130-second modified layer; 140-first heat conductive layer; 150-second heat conductive layer; 160-first metal layer; 170-second metal layer. DETAILED DESCRIPTION
[0049] The following is a further complete and clear description of the polymer composite film, composite current collector and preparation method thereof, positive electrode and application of the present application in conjunction with specific examples. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0050] At present, power batteries generally take high energy density and high rate as their iterative development goals, which simultaneously brings about the urgent need for high safety of power batteries under high energy density. This application found that the positive electrode sheet is at a higher potential during the battery charging and discharging process and participates in complex redox reactions. Its chemical stability is crucial to the thermal stability of the battery; high energy density positive electrode materials are often more active and more prone to thermal runaway, and the specific capacity and structural stability of the positive electrode material directly affect the energy density and cycle performance of the battery. Once the positive electrode material has problems such as structural collapse, it will not only lead to a decline in battery performance, but may also cause serious safety accidents such as internal short circuits; in addition, the interface reaction between the positive electrode material and the electrolyte may also produce gas, heat, etc., further threatening the safety of the battery. Therefore, compared with other battery components such as negative electrodes, positive electrodes have a greater impact on the safety of power batteries.
[0051] The positive electrode current collector is an important component of the positive electrode sheet. At present, the positive electrode current collector aluminum foil mainly adopts a sandwich structure of "metal-polymer material-metal", with PET polymer material as the middle layer, and aluminum or copper metal deposited on the upper and lower layers to form a metal conductive layer. The elongation of pure aluminum material is 10% to 30%, and the elongation of PET material is generally more than 80%. The overall elongation at break of the composite current collector aluminum foil is mainly determined by the PET film material. The excessive elongation at break makes it impossible for the composite aluminum foil to be disconnected immediately when it is damaged by external force, which is not conducive to controlling battery thermal runaway. Therefore, reducing the elongation of the composite current collector can prevent the occurrence of battery thermal runaway.
[0052] Based on this, the first aspect of this application, refer to Figure 1 , a polymer composite film 10 is provided, wherein the polymer composite film 10 includes a polymer base layer 110 and a first modified layer 120 and a second modified layer 130 respectively disposed on opposite side surfaces of the polymer base layer 110 .
[0053] The material of the polymer base layer 110 includes one or more of polyethylene terephthalate, polyethylene terephthalate-1,4-cyclohexanedimethanol and polyethylene terephthalate-1,4-cyclohexanedimethanol.
[0054] The components of the first modified layer and the second modified layer each independently include: a functionalized polymer material.
[0055] The functionalized polymer material includes one or more of polyethylene naphthalate, poly(m-phenylene adipamide), liquid crystal polymer, polyoxymethylene, polyphenylene sulfide and polyphenylene ether.
[0056] Liquid crystal polymer (LCP) is a polymer material composed of liquid crystal molecules and polymer matrix. Its structure mainly consists of two parts: a rigid rod-shaped liquid crystal unit and a flexible chain-shaped polymer skeleton. Rigid rod-shaped LCP has the characteristics of spontaneous orientation, and because LCP is a linear polymer with a tight interchain stacking structure, it exhibits high strength, high modulus, outstanding heat resistance and excellent dimensional stability.
[0057] The polymer composite film provided by the present application can be used as a base film of a composite current collector, which can effectively reduce the elongation of PET materials, so it can effectively prevent the occurrence of thermal runaway of batteries. Specifically, the polymer composite film provided by the present application includes a first modified layer and a second modified layer respectively arranged on the surfaces of the opposite sides of the polymer base layer, and the components of the first modified layer and the second modified layer include a specific type of functionalized polymer material, wherein the specific type of functionalized polymer material and the polymer base layer of the specific material cooperate with each other, so that the first modified layer and the second modified layer can form a film layer with lower elongation at break and higher tensile strength on the surface of the polymer base layer. In addition, the inventors found that by setting the first modified layer and the second modified layer on the surfaces of the opposite sides of the polymer base layer, on the one hand, the film-forming property of the polymer composite film can be retained, and the composite film can be prevented from breaking due to excessive rigidity during the film drawing process. On the other hand, the modified layer cannot achieve a high degree of crystallinity in the film drawing stage. Setting the modified layer on the surface of the polymer base layer is conducive to further crystallization in the subsequent heat treatment stage of preparing the composite current collector evaporation, thereby reducing the elongation, and the modified layer set on the surface of the polymer base layer can significantly improve the temperature resistance of the composite film. Under higher heat treatment conditions, it can ensure a higher degree of crystallinity and prevent thermal shrinkage and deformation of the composite film. Furthermore, the lower elongation at break of the first modified layer and the second modified layer makes it easier for the polymer composite film of the present application to break when it is used as a battery current collector base film under the action of external force, and then the abnormal current path inside the battery can be cut off in time, effectively avoiding battery thermal runaway caused by continuous power supply, and significantly improving the safety performance of the battery.
[0058] In addition, the addition of the first modified layer and the second modified layer can also enhance the bonding force with the metal layer, and the polymer composite film of the present application can reduce its thermal shrinkage performance, which is beneficial to the process of preparing the metal layer by evaporation coating.
[0059] Preferably, the functionalized polymer material comprises one or more of polyethylene naphthalate, poly(m-phenylene adipamide) and polyphenylene sulfide. The structure of polyethylene naphthalate (PEN) is similar to that of PET, wherein the naphthalene ring with greater rigidity replaces the benzene ring in PET. Since the naphthalene ring has a more stable resonance structure than the benzene ring, the rigidity of the PEN molecular chain is greater, and its glass transition temperature, crystallization temperature and melting point are all higher than those of PET. In addition, the tensile strength of PEN is 35% higher than that of PET, the flexural modulus is about 50% higher, the molding heat shrinkage is small, and the dimensional stability is good.
[0060] More preferably, the functionalized polymer material includes one or more of poly(meta-phenylene adipamide) and poly(phenylene sulfide).
[0061] Poly(m-phenylene adipamide) (MXD6) is a semi-crystalline, semi-aromatic polyamide. There are rigid m-phenyl groups on the main chain of MXD6, and the amide groups in the molecular chain can form intermolecular hydrogen bonds. It has the advantages of high dimensional stability, low moisture absorption, strong rigidity, wide operating temperature range, and small thermal expansion coefficient. The presence of benzene ring structure makes MXD6 less tough, and the notched impact strength is only about 20J / m. It is a hard and brittle material.
[0062] In one example, the components of the first modified layer and the second modified layer independently include: a polyterephthalate polymer, an anti-blocking agent, and a functionalized polymer material.
[0063] Furthermore, the raw materials for preparing the first modified layer and the second modified layer independently include: an anti-adhesive masterbatch and a modified masterbatch in a mass ratio of (1-5):(95-99).
[0064] Wherein, in the anti-blocking masterbatch, the mass ratio of the anti-blocking agent to the polyterephthalate polymer is (0.1~5):(95~99.9).
[0065] Wherein, in the modified masterbatch, the mass ratio of the functionalized polymer material to the polyterephthalate polymer is (20-60): (40-80).
[0066] Among the raw materials for the preparation of the present application, an anti-adhesion masterbatch including an anti-adhesion agent and a poly(terephthalate) polymer and a modified masterbatch including a functionalized polymer material and a poly(terephthalate) polymer are selected. Among them, the anti-adhesion masterbatch can ensure the anti-adhesion effect between the polymer base layer and the modified layer, and can ensure sufficient rigidity enhancement modification effect of the modified layer. The modified material helps to improve the brittleness of the modified layer, thereby reducing the elongation at break of the modified layer. It can be understood that in the present application, the mass ratio of the anti-adhesion masterbatch and the modified masterbatch includes but is not limited to 1:99, 1.5:98.5, 2:98, 2.5:97.5, 3:97, 3.5:96.5, 4:96, 4.5:95.5 or 5:95, or within the range formed by any two of the above point values as endpoint values. If the content of the anti-adhesion masterbatch is too low, the composite films will stick to each other when winding and unwinding. If the content of the anti-adhesion masterbatch is too high, the composite film may break easily when the film is pulled, affecting the yield.
[0067] Furthermore, in the anti-blocking masterbatch, the mass ratio of the anti-blocking agent to the poly(terephthalate) polymer is (0.1-5):(95-99.9). The content of the anti-blocking agent within this range can ensure sufficient anti-blocking effect between the modified layers. Furthermore, the mass ratio of the anti-blocking agent to the poly(terephthalate) polymer includes but is not limited to 0.1:99.9, 0.5:99.5, 1:99, 2:98, 3:97, 4:96 or 5:95, or a range formed by any two of the above points as endpoint values.
[0068] Preferably, in the anti-blocking masterbatch, the mass ratio of the anti-blocking agent to the polyterephthalate polymer is (3-5): (95-97).
[0069] Further, in the modified masterbatch, the mass ratio of the functionalized polymer material to the polyester terephthalate polymer is (20~60): (40~80). The mass percentage of the functionalized polymer material within this range can ensure sufficient modification effect. If the amount of the functionalized polymer material added is slightly less, it is easy to cause the elongation at break of the modified layer to decrease insignificantly; if the amount of the functionalized polymer material added is slightly more, the risk of film breakage of the polymer composite film will increase. For example, the mass ratio of the functionalized polymer material to the polyester terephthalate polymer includes but is not limited to 20:80, 25:75, 30:70, 35:65, 40:60, 45:55, 50:50, 55:45, or 60:40, or within the range formed by any two of the above point values as endpoint values. Further, the mass ratio of the functionalized polymer material to the polyester terephthalate polymer is (50~60): (40~50).
[0070] In one example, the polyethylene terephthalate polymer includes one or more of polyethylene terephthalate, polyethylene terephthalate-1,4-cyclohexanedimethanol and polyethylene terephthalate-1,4-cyclohexanedimethanol.
[0071] Preferably, the polyethylene terephthalate polymer includes polyethylene terephthalate.
[0072] Preferably, the material of the polymer base layer includes polyethylene terephthalate.
[0073] In one example, the anti-adhesive agent includes one or more of silicon dioxide, glass microspheres, calcium carbonate and talc.
[0074] In one example, the thickness of the polymer base layer is 3μm to 15μm. When the thickness of the polymer base layer is within a reasonable range, the appropriate thickness can provide ideal mechanical strength and flexibility, making the composite current collector less prone to cracking, wrinkling and other problems during battery production and use, and enhancing structural stability; furthermore, the appropriate thickness is conducive to controlling the weight and cost of the entire composite current collector, achieving lightweight design and reducing material costs while meeting performance requirements; in addition, accurately defining the thickness can also optimize the internal space layout of the battery, increase the energy density of the battery, and thus improve the overall performance of the battery.
[0075] In one example, the thickness ratio of the first modified layer and the polymer base layer is (0.6~1.4):(3.2~4.8). Defining the thickness ratio of the first modified layer and the polymer base layer is important for ensuring that the modification effect of the modified layer on the polymer base layer does not affect the film-forming stability of the polymer composite film. For example, the thickness ratio of the first modified layer and the polymer base layer includes but is not limited to 0.6:4.8, 0.8:4.4, 1:4, 1.2:3.6 or 1.4:3.2, or within the range formed by any two of the above point values as endpoint values.
[0076] In one example, the thickness ratio of the second modified layer to the polymer base layer is (0.6-1.4):(3.2-4.8). Further, the thickness ratio of the second modified layer to the polymer base layer includes but is not limited to 0.6:4.8, 0.8:4.4, 1:4, 1.2:3.6 or 1.4:3.2, or a range formed by any two of the above point values as endpoint values.
[0077] In one example, the raw materials for preparing the first modified layer and the second modified layer independently further include: a nucleating agent. Adding a nucleating agent to the raw materials for preparing the first modified layer and the second modified layer can significantly accelerate the crystallization rate during the preparation of the polymer composite film, so as to improve the crystallinity and mechanical properties of the polymer composite film and reduce its elongation.
[0078] In one example, the mass ratio of the nucleating agent to the functionalized polymer material is (1-5): (20-60). A suitable mass ratio can enable the nucleating agent to better play a heterogeneous nucleation role, provide more nuclei for the crystallization of the functionalized polymer material, accelerate the crystallization rate, make the crystal structure more regular, fine and uniform, thereby improving the crystallinity and reducing the elongation at break of the modified layer. For example, the mass ratio of the nucleating agent to the functionalized polymer material includes but is not limited to 1:20, 2:30, 4:50, 5:50, 5:52, 5:56, 5:57, 5:58 or 5:60, or within the range formed by any two of the above point values as endpoint values.
[0079] In one example, the nucleating agent includes one or more of calcium carbonate, layered double metal hydroxide, boron nitride, zinc oxide, dibenzylidene sorbitol and aryl dicarbonamide.
[0080] In one example, the polymer base layer does not include a nucleating agent.
[0081] The present application finds that when a relatively excessive amount of nucleating agent is added to the first modified layer and the second modified layer, and when a nucleating agent is not added to the polymer base layer, it is more conducive to the preparation of polymer composite film and composite current collector. Specifically, in the process of preparing polymer composite film, due to the formation of a micro-melt blend with a specific layered structure after melt blending with the preparation raw materials of the first modified layer, the polymer base film and the second modified layer, and the step of stretching the micro-melt blend, the stretching treatment can provide power for the excessive nucleating agent in the first modified layer and the second modified layer to contact each other with the polymer base film, and the diffusion migration of the excessive nucleating agent into the polymer base film, thereby making the unreacted nucleating agent in the first modified layer and the second modified layer enter the polymer base layer. Since the nucleating agent of the modified layer enters the polymer base layer, it is already the second half of the film pulling, and the time to maintain high temperature is short at this time, the nucleating agent and the polymer base layer will not react completely, and the vacuum evaporation process will maintain a higher temperature and a longer time, and the nucleating agent entering the polymer base layer will further crystallize with the polymer base layer during the evaporation process, thereby reducing the elongation of the polymer base layer appropriately. In addition, the reason why excessive nucleating agent is not directly added to the polymer base layer is that the reaction rate of the polymer base layer with the nucleating agent is faster than the reaction rate of the modified layer with the nucleating agent. Directly adding the nucleating agent to the polymer base layer will cause the nucleating agent in the polymer base layer to react completely during the stretching process, making the crystallinity of the composite film too high, which causes the polymer composite film to break easily after the stretching process during the preparation process, and then leads to a decrease in the preparation yield of the polymer composite film. At the same time, when the polymer composite film is used as a base film in the evaporation process of the composite current collector metal layer, it also has the disadvantage of being difficult to withstand the thermal stress or mechanical stress of the evaporation, and thus prone to film breakage.
[0082] See also Figure 2 In one example, the polymer composite film further includes: a first heat-conducting layer 140 and a second heat-conducting layer 150 .
[0083] The first heat-conducting layer 140 is disposed on a surface of the first modified layer 120 that is away from the polymer base layer 110 .
[0084] The second heat conductive layer 150 is disposed on a surface of the second modified layer 130 that is away from the polymer base layer 110 .
[0085] In one example, the first heat-conducting layer and the second heat-conducting layer are provided by spraying or magnetron sputtering, and the materials of the first heat-conducting layer and the second heat-conducting layer are independently selected from one or more of metal materials, carbon-based materials and non-metal carbides. For example, the metal materials of the first heat-conducting layer and the second heat-conducting layer include but are not limited to copper, aluminum or silver. The carbon-based materials of the first heat-conducting layer and the second heat-conducting layer include but are not limited to graphene or carbon nanotubes. The non-metal carbide materials of the first heat-conducting layer and the second heat-conducting layer include but are not limited to silicon carbide or boron carbide.
[0086] Preferably, the first heat-conducting layer and the second heat-conducting layer are provided so that heat can be quickly transferred to the polymer base layer when the metal layer is prepared, so that the nucleating agent can crystallize the polymer base layer with the help of the heat.
[0087] In one example, the thickness of the first heat-conducting layer and the second heat-conducting layer are independently selected from 30 nm to 70 nm. For example, the thickness of the first heat-conducting layer and the second heat-conducting layer includes but is not limited to 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm or 70 nm, or a range formed by any two of the above points as endpoint values.
[0088] The present application also provides a method for preparing a polymer composite film, comprising the following steps:
[0089] The first modified layer, the polymer base film, the second modified layer and the raw materials for preparation are mixed independently, melt-extruded and sliced to prepare a first mixed material, a second mixed material and a third mixed material respectively;
[0090] The first mixed material, the second mixed material and the third mixed material are melt-blended and extruded to prepare a mixed material;
[0091] The blended material is stretched to prepare a polymer composite film.
[0092] The polymer composite film comprises a polymer base layer and a first modified layer and a second modified layer respectively arranged on two opposite side surfaces of the polymer base layer.
[0093] In a second aspect of the present application, a composite current collector is provided, comprising the polymer composite film as described in any example of the first aspect of the present application, and a metal layer disposed on at least one surface of the polymer composite film.
[0094] The present application found that reducing the elongation at break of the positive electrode current collector rather than the negative electrode current collector has a positive effect on preventing thermal runaway. Based on this, in one example, the material of the metal layer includes one or more of aluminum and aluminum alloy.
[0095] In one example, the metal layer includes a first metal layer and a second metal layer.
[0096] See also Figure 3 In one example, the positive electrode current collector includes a first metal layer 160, a first modified layer 120, a polymer base layer 110, a second modified layer 130 and a second metal layer 170 which are stacked.
[0097] See also Figure 4 In one example, the positive electrode current collector includes a first metal layer 160, a first thermal conductive layer 140, a first modified layer 120, a polymer base layer 110, a second modified layer 130, a second thermal conductive layer 150 and a second metal layer 170 which are stacked.
[0098] In one example, the thickness of the metal layer is 0.8μm~1.2μm. This thickness range can ensure that the metal layer has good conductivity, can effectively reduce the internal resistance of the battery, and improve the charging and discharging efficiency and performance stability of the battery; it can provide sufficient mechanical strength, so that the composite current collector is not prone to cracking, deformation and other problems during battery production and use, thereby enhancing the reliability of the overall structure. In addition, the metal layer and the polymer composite film within this thickness range have good compatibility, which can effectively ensure that the composite current collector has a lower elongation at break. For example, the thickness of the metal layer includes but is not limited to 0.8μm, 0.9μm, 1μm, 1.1μm or 1.2μm, or within the range formed by any two of the above point values as endpoint values.
[0099] The third aspect of the present application provides a method for preparing the composite current collector according to the second aspect of the present application, comprising the following steps:
[0100] The material of the metal layer is vacuum-evaporated on at least one side of the surface of the polymer composite film to prepare the composite current collector.
[0101] In one example, the material of the metal layer is aluminum, and the diameter of the aluminum is 1 mm to 3 mm.
[0102] For example, the vacuum evaporation equipment includes but is not limited to an evaporation boat. More for example, the vacuum evaporation equipment is 72 sets of evaporation boats.
[0103] In one example, the process parameters of the vacuum evaporation include: the wire feeding speed of the material of the metal layer is 400 mm / min~500 mm / min. For example, the wire feeding speed of the material of the metal layer includes but is not limited to 400 mm / min, 410 mm / min, 420 mm / min, 430 mm / min, 440 mm / min, 450 mm / min, 460 mm / min, 470 mm / min, 480 mm / min, 490 mm / min or 500 mm / min, or a range formed by any two of the above point values as endpoint values.
[0104] In one example, the evaporation rate of the vacuum evaporation is 10 m / min to 20 m / min. The evaporation rate within the above range can ensure production efficiency while ensuring the yield of the evaporation product and avoid excessive production costs. For example, the evaporation rate includes but is not limited to 10 m / min, 12 m / min, 15 m / min, 18 m / min or 20 m / min, or any two of the above points as endpoint values.
[0105] In one of the examples, the evaporation power of the vacuum evaporation is 7kW~12kW. The evaporation power of vacuum evaporation is generally about 5kW. The evaporation power of the present application can ensure sufficient heat treatment effect within the above range. If the evaporation power is too large, the polymer composite film will be thermally damaged too much, and its tensile strength will be significantly reduced. If the evaporation power is too small, the crystallinity of the polymer composite film will be insufficient, resulting in an insignificant decrease in its elongation. By way of example, the evaporation power of vacuum evaporation includes but is not limited to 7 kW, 7.5 kW, 8 kW, 8.5 kW, 9 kW, 9.5 kW, 10 kW, 10.5 kW, 11kW, 11.5kW or 12kW, or within the range of any two of the above point values.
[0106] In one example, the temperature of the main roller of the vacuum evaporation is -20°C~0°C. The temperature of the main roller of the evaporation is coordinated with the evaporation power within the above range to ensure sufficient heat treatment effect, so as to prevent the shortcomings of high elongation of the polymer composite film caused by insufficient heat treatment effect and insufficient crystallinity. At the same time, it can prevent the main roller temperature of the evaporation from being too high, and the heat cannot be dissipated in time, resulting in excessive thermal damage and reduced tensile strength. By way of example, the temperature of the main roller of the vacuum evaporation includes but is not limited to -20°C, -18°C, -16°C, -14°C, -12°C, -10°C, -8°C, -6°C, -4°C, -2°C or 0°C, or within the range of any two of the above point values.
[0107] In one example, the reeling tension and unwinding tension of the vacuum evaporation are independently 100N~300N. The reeling and unwinding tensions within the above range can accelerate the optimization of the heat treatment effect and ensure a good reeling effect and appearance quality. For example, the reeling tension and unwinding tension of the vacuum evaporation independently include but are not limited to 100N, 110N, 120N, 150N, 180N, 200N, 220N, 250N, 270N, 280N or 300N, or any two of the above points as the endpoint values.
[0108] In one example, the distance between the evaporation boat of the vacuum evaporation and the polymer composite film is 250 mm to 350 mm. The distance between the evaporation boat and the polymer composite film within the above range can ensure the heat treatment effect and prevent the polymer composite film from being excessively damaged by heat. For example, the distance between the evaporation boat of the vacuum evaporation and the polymer composite film includes but is not limited to 250 mm, 270 mm, 290 mm, 310 mm, 330 mm or 350 mm, or any two of the above points as endpoint values.
[0109] In a fourth aspect of the present application, a positive electrode is provided, comprising the composite current collector described in the second aspect of the present application.
[0110] In a fifth aspect of the present application, a battery is provided, comprising the positive electrode described in the fourth aspect.
[0111] In a sixth aspect of the present application, there is provided an electrical device comprising the battery described in the fifth aspect.
[0112] The following further specific examples are provided to explain the present application in detail. It should also be understood that the following examples are only used to further explain the present application and cannot be understood as limiting the scope of protection of the present application. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present application belong to the scope of protection of the present application. The specific process parameters of the following embodiments are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not necessarily limited to the specific values of the embodiments below.
[0113] Example 1
[0114] Example 1 of the present application provides a polymer composite film, a composite current collector and a preparation method thereof.
[0115] Polymer composite film: The polymer composite film includes a polymer base layer and a first modified layer and a second modified layer respectively disposed on the surfaces of the polymer base layer on opposite sides; wherein the material of the polymer base layer is a PET layer with a thickness of 6 μm; the thickness ratio of the first modified layer to the polymer base layer is 1.4:3.2, and the thickness ratio of the second modified layer to the polymer base layer is 1.4:3.2. wherein the raw materials for preparing the first modified layer and the second modified layer both include: an anti-adhesive masterbatch and a modified masterbatch in a ratio of 5:95. the components of the anti-adhesive masterbatch include 1% silicon dioxide and 99% PET material. the components of the modified masterbatch include 60% polyethylene naphthalate and 40% PET material.
[0116] A composite current collector and a preparation method thereof: using 72 groups of evaporation boats and aluminum wires with a diameter of 2 mm, the aluminum wires are vacuum evaporated onto the surfaces of both sides of a polymer composite film to prepare a first metal layer and a second metal layer respectively, the first metal layer is arranged on the surface of the first modified layer on the side away from the polymer base layer, the second metal layer is arranged on the surface of the second modified layer on the side away from the polymer base layer, and the thickness of the first metal layer and the second metal layer is 1 μm; a composite current collector is obtained.
[0117] Among them, the process parameters of vacuum evaporation include: aluminum wire feeding speed 450mm / min, evaporation rate 15m / min, evaporation power 8kW, evaporation main roller temperature -10℃, evaporation winding and unwinding tension 200N, and the distance between the vacuum evaporation evaporation boat and the polymer composite film is 300mm.
[0118] Example 2
[0119] The polymer composite membrane of Example 2 of the present application is basically the same as Example 1, with the main difference being that the raw materials for preparing the first modified layer and the second modified layer of the polymer composite membrane of Example 2 further include a nucleating agent.
[0120] The polymer composite film of Example 2 includes a polymer base layer and a first modified layer and a second modified layer respectively arranged on the surfaces of the opposite sides of the polymer base layer; wherein the material of the polymer base layer is a PET layer with a thickness of 6 μm; the thickness ratio of the first modified layer to the polymer base layer is 1.4:3.2, and the thickness ratio of the second modified layer to the polymer base layer is 1.4:3.2. wherein the raw materials for preparing the first modified layer and the second modified layer both include: an anti-adhesive masterbatch, a modified masterbatch and a nucleating agent in a ratio of 5:95:5. the components of the anti-adhesive masterbatch include 1% silicon dioxide and 99% PET material. the components of the modified masterbatch include 60% polyethylene naphthalate and 40% PET material. the type of the nucleating agent is calcium carbonate.
[0121] Composite current collector and preparation method thereof: same as in Example 1.
[0122] Example 3
[0123] The polymer composite film of Example 3 of the present application is basically the same as that of Example 2, with the main difference being that the polymer composite film of Example 3 further includes a first heat-conducting layer and a second heat-conducting layer.
[0124] The polymer composite film of Example 3 includes a first heat-conducting layer (silicon carbide), a first modified layer, a polymer base layer, a second modified layer and a second heat-conducting layer (silicon carbide) stacked in layers. Among them, the material of the polymer base layer is a PET layer with a thickness of 6μm; the thickness of the first heat-conducting layer and the second heat-conducting layer is 50nm, the thickness ratio of the first modified layer to the polymer base layer is 1.4:3.2, and the thickness ratio of the second modified layer to the polymer base layer is 1.4:3.2. Among them, the raw materials for preparing the first modified layer and the second modified layer both include: an anti-adhesive masterbatch, a modified masterbatch and a nucleating agent in a ratio of 5:95:5. The components of the anti-adhesive masterbatch include 1% silicon dioxide and 99% PET material. The components of the modified masterbatch include 60% polyethylene naphthalate and 40% PET material. The type of nucleating agent is calcium carbonate.
[0125] Composite current collector and preparation method thereof
[0126] Using 72 groups of evaporation boats and aluminum wires with a diameter of 2 mm, the aluminum wires were vacuum evaporated onto the two side surfaces of the polymer composite film to prepare the first metal layer and the second metal layer respectively. The first metal layer was arranged on the side of the first thermal conductive layer away from the first modified layer, and the second metal layer was arranged on the side of the second thermal conductive layer away from the second modified layer. The thickness of the first metal layer and the second metal layer was 1 μm. A composite current collector was obtained.
[0127] Among them, the process parameters of vacuum evaporation include: aluminum wire feeding speed 450mm / min, evaporation rate 15m / min, evaporation power 8kW, evaporation main roller temperature -10℃, evaporation winding and unwinding tension 200N, and the distance between the vacuum evaporation evaporation boat and the polymer composite film is 300mm.
[0128] Example 4
[0129] Polymer composite film: Same as Example 3, the main difference is that the modified masterbatch of Example 4 includes 60% poly(m-phenylene adipamide) and 40% PET material.
[0130] Composite current collector and preparation method thereof: same as Example 3.
[0131] Example 5
[0132] Polymer composite film: Same as Example 3, the main difference is that the modified masterbatch of Example 5 includes 60% polyphenylene sulfide and 40% PET material.
[0133] Composite current collector and preparation method thereof: same as Example 3.
[0134] Example 6
[0135] Polymer composite film: Same as Example 3, the main difference is that the components of the modified masterbatch of Example 6 include 40% polyethylene naphthalate and 60% PET material.
[0136] Composite current collector and preparation method thereof: same as Example 3.
[0137] Example 7
[0138] Polymer composite film: Same as Example 3, the main difference is that the components of the modified masterbatch of Example 7 include 20% polyethylene naphthalate and 80% PET material.
[0139] Composite current collector and preparation method thereof: same as Example 3.
[0140] Example 8
[0141] Polymer composite film: Same as Example 3, the main difference is that the components of the anti-blocking masterbatch of Example 8 include 3% silicon dioxide and 97% PET material.
[0142] Composite current collector and preparation method thereof: same as Example 3.
[0143] Example 9
[0144] Polymer composite film: Same as Example 3, the main difference is that the components of the anti-blocking masterbatch of Example 9 include 5% silicon dioxide and 95% PET material.
[0145] Composite current collector and preparation method thereof: same as Example 3.
[0146] Comparative Example 1
[0147] Polymer base layer: The material of the polymer base layer is a PET layer with a thickness of 6 μm.
[0148] Composite current collector and preparation method thereof: using 72 groups of evaporation boats and aluminum wire with a diameter of 2 mm, vacuum evaporating the aluminum wire on the two side surfaces of the polymer base layer to prepare the first metal layer and the second metal layer respectively, the thickness of the first metal layer and the second metal layer is 1 μm; obtaining a composite current collector.
[0149] Among them, the process parameters of vacuum evaporation include: aluminum wire feeding speed 450mm / min, evaporation rate 15m / min, evaporation power 8kW, evaporation main roller temperature -10℃, evaporation winding and unwinding tension 200N, and the distance between the vacuum evaporation evaporation boat and the polymer composite film is 300mm.
[0150] Performance Test:
[0151] Composite current collector mechanical properties test
[0152] The composite current collectors prepared in Examples 1 to 9 and Comparative Example 1 were tested for tensile strength and elongation at break. The composite current collectors to be tested were cut into test strips using a strip cutting machine. Ten test strips were cut from each group of test samples in each example. The test strips had a width of 15 mm, a length of 150 mm, a stretching rate of 100 mm / min, and a tensile chuck spacing of 100 mm. The tensile strength and elongation at break data in the MD direction were tested and the average values were taken. The test data are shown in Table 1.
[0153] Table 1
[0154]
[0155] Battery collision safety performance test
[0156] The ternary active material NCM811, conductive carbon black and binder PVDF were mixed in NMP at a weight ratio of 93:2:5 to obtain positive electrode slurry. The positive electrode slurry was coated on the current collector sample of the embodiment or comparative example, dried, rolled and die-cut to obtain positive electrode sheets.
[0157] The negative electrode active material artificial graphite, binder SBR, dispersant CMC and conductive carbon black are mixed in water at a weight ratio of 95.5:2.3:1.5:0.7 and then mixed to obtain a negative electrode slurry. The negative electrode slurry is coated on copper foil, dried, rolled and die-cut to obtain a negative electrode sheet.
[0158] The positive electrode sheet, separator (PE film), and negative electrode sheet are stacked in order, and the battery cell is obtained after winding, and placed in the battery case. The electrolyte (lithium salt LiPF 6 , concentration is 1 mol / L, carbonate solvent), and after packaging, a battery sample is obtained.
[0159] The battery samples obtained from the composite current collectors prepared in Examples 1 to 9 and Comparative Example 1 were respectively subjected to collision safety performance tests.
[0160] (1) Battery pretreatment
[0161] Fully charge the packaged battery sample to the rated capacity (SOC=100%) and leave it for more than 4 hours to eliminate the polarization effect. During battery production, a temperature measurement hole is reserved and a micro thermocouple is placed for temperature measurement.
[0162] (2) Battery fixing
[0163] Fix the battery sample on the test bench with a three-point clamp and install a metal pendulum on the test bench to ensure that the battery axis is completely perpendicular to the pendulum's motion trajectory. Mark the center of impact on the front of the battery.
[0164] (3) Crash test
[0165] Release the pendulum and allow it to hit the center point of the front of the battery three times in free fall motion. Record the temperature value inside the battery sample 10 minutes after the impact. The test data is shown in Table 2.
[0166] Table 2
[0167]
[0168] As can be seen from Table 1, the composite current collector prepared in the embodiment of the present application has a higher tensile strength than that in Comparative Example 1, which indicates that the composite current collector in the embodiment of the present application has a good ability to resist tensile damage. At the same time, the composite current collector prepared in the embodiment of the present application has a lower elongation at break than that in Comparative Example 1, which indicates that the deformation experienced by the composite current collector from the beginning of force to fracture during the stretching process is small, and the ductility of the composite current collector is poor, which makes it easier for the composite current collector in the embodiment of the present application to break when the battery is assembled into a battery under the action of external forces such as battery breakdown and battery collision, and then the abnormal passage inside the battery can be cut off in time, so that the battery cell is disconnected and the temperature of the battery cell is suppressed.
[0169] Example 1 is basically the same as Example 2, the main difference being that a nucleating agent is also added to Example 2. From the test results in Tables 1 and 2, the tensile strength of the composite current collector of Example 2 is relatively high, indicating that the composite current collector of Example 2 has excellent tensile damage resistance; and the elongation at break of the composite current collector of Example 2 is relatively low, indicating that the material damage limit will be reached under a relatively small deformation. It can be further seen from Table 2 that the battery cell temperature of Example 2 is relatively low, indicating that when the composite current collector of Example 2 is damaged by external forces such as collisions, there are more short circuits inside the battery cell, so the battery cell temperature is lower, and the battery cell safety performance of Example 2 is more excellent.
[0170] In Example 3, a heat-conducting layer is added, and the tensile strength is higher and the elongation at break is lower than that in Example 2, and the battery core temperature is also lower. This shows that compared with Example 2, the battery core safety performance of Example 3 is better.
[0171] Embodiment 3, embodiment 4 and embodiment 5 are basically the same, and the main difference is that the types of functionalized polymer materials are different. From the technical effect point of view, the safety performance of embodiment 4 in which the functionalized polymer material is poly(m-phenylene adipamide) is better than that of embodiment 5 in which the functionalized polymer material is polyphenylene sulfide and embodiment 3 in which the functionalized polymer material is polyethylene naphthalate.
[0172] Embodiment 3, embodiment 6 and embodiment 7 are basically the same, and the main difference is that the content of each component in the modified masterbatch is different. In embodiment 3, when the mass ratio of the functionalized polymer material to the PET material is 60:40, the safety performance of the battery cell is more excellent.
[0173] Embodiment 3, Embodiment 8 and Embodiment 9 are basically the same, and the main difference is that the content of each component in the anti-adhesion masterbatch is different. In Embodiment 9, when the mass ratio of the anti-adhesion agent to the PET material is 5:95, the safety performance of the battery cell is more excellent.
[0174] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0175] The above-described embodiments only express several implementation methods of the present application, which is convenient for understanding the technical solution of the present application in detail, but it cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several modifications and improvements can be made, which all belong to the scope of protection of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the scope of protection of the claims attached to the present application. Therefore, the scope of protection of the patent of this application shall be based on the content of the attached claims, and the description can be used to interpret the content of the claims.
Claims
1. A polymer composite film, characterized in that The polymer composite film comprises a polymer base layer and a first modified layer and a second modified layer respectively disposed on two opposite side surfaces of the polymer base layer; The material of the polymer base layer includes one or more of polyethylene terephthalate, polyethylene terephthalate-1,4-cyclohexanedimethanol and polyethylene terephthalate-1,4-cyclohexanedimethanol; The components of the first modified layer and the second modified layer each independently include: a functionalized polymer material; The functionalized polymer material includes one or more of polyethylene naphthalate, poly(m-phenylene adipamide), liquid crystal polymer, polyoxymethylene, polyphenylene sulfide and polyphenylene ether.
2. The polymer composite membrane according to claim 1, characterized in that The components of the first modified layer and the second modified layer independently include: a polyterephthalate polymer, an anti-blocking agent and a functionalized polymer material.
3. The polymer composite membrane according to claim 2, characterized in that The raw materials for preparing the first modified layer and the second modified layer independently include: an anti-adhesive masterbatch and a modified masterbatch in a mass ratio of (1-5): (95-99); The anti-blocking masterbatch comprises the polyterephthalate polymer and the anti-blocking agent; Wherein, in the anti-blocking masterbatch, the mass ratio of the anti-blocking agent to the polyterephthalate polymer is (0.1-5): (95-99.9); The modified masterbatch comprises the polyterephthalate polymer and the functionalized polymer material; Among them, in the modified masterbatch, the mass ratio of the functionalized polymer material to the polyester terephthalate polymer is (20~60): (40~80).
4. The polymer composite membrane according to claim 2 or 3, characterized in that: The polyethylene terephthalate polymer includes one or more of polyethylene terephthalate, polyethylene terephthalate-1,4-cyclohexanedimethanol and polyethylene terephthalate-1,4-cyclohexanedimethanol; And / or, the anti-adhesive agent includes one or more of silicon dioxide, glass microspheres, calcium carbonate and talc.
5. The polymer composite film according to any one of claims 1 to 3, characterized in that: The polymer composite film has one or more of the following characteristics: (1) The thickness ratio of the first modified layer to the polymer base layer is (0.6-1.4): (3.2-4.8); (2) The thickness ratio of the second modified layer to the polymer base layer is (0.6-1.4):(3.2-4.8).
6. The polymer composite membrane according to claim 1, characterized in that The raw materials for preparing the first modified layer and the second modified layer independently further include: a nucleating agent; the nucleating agent has one or more of the following characteristics: (1) The mass ratio of the nucleating agent to the functionalized polymer material is (1-5): (20-60); (2) The nucleating agent includes one or more of calcium carbonate, layered double metal hydroxide, boron nitride, zinc oxide, dibenzylidene sorbitol and aryl dicarbonamide.
7. The polymer composite membrane according to claim 1, 2, 3 or 6, characterized in that: The polymer composite film further comprises: a first heat-conducting layer and a second heat-conducting layer; Wherein, the first heat-conducting layer is arranged on a surface of the first modified layer which is away from the polymer base layer; The second heat-conducting layer is disposed on a surface of the second modified layer that is away from the polymer-based layer.
8. A composite current collector, characterized in that: The composite current collector comprises the polymer composite film according to any one of claims 1 to 7, and a metal layer disposed on at least one surface of the polymer composite film.
9. The composite current collector according to claim 8, characterized in that: The material of the metal layer includes one or more of aluminum and aluminum alloy; And / or, the thickness of the metal layer is 0.8 μm to 1.2 μm.
10. A method for preparing the composite current collector according to claim 8 or 9, characterized in that: The following steps are involved: Vacuum evaporating the material of the metal layer on at least one side surface of the polymer composite film to prepare the composite current collector; The process parameters of the vacuum evaporation have one or more of the following characteristics: (1) The wire feeding speed of the material of the metal layer is 400 mm / min~500 mm / min; (2) The vacuum evaporation rate is 10 m / min to 20 m / min; (3) The vacuum evaporation power is 7 kW to 12 kW; (4) The temperature of the main roller of the vacuum evaporation is -20°C to 0°C; (5) The rewinding tension and unwinding tension of the vacuum evaporation are independently 100N~300N; (6) The distance between the heat source of the vacuum evaporation and the polymer composite film is 250 mm to 350 mm.
11. A positive electrode, characterized in that: Comprising the composite current collector according to claim 8 or 9.
12. A battery, characterized in that: Comprising the positive electrode according to claim 11.
13. An electrical device, characterized in that: Comprising the battery as claimed in claim 12.
Citation Information
Patent Citations
Solvent-resistant enhanced polyester film, preparation method thereof, composite current collector and application
CN115322534A
Composite current collector
CN119092715A
Polyester film for lithium ion battery power collector, film foil for lithium ion battery power collector, and lithium ion battery power collector
JP2024134250A
Cited By
Polyester composite film and preparation method thereof, composite current collector and preparation method thereof, electrode and application thereof
CN120327063A